Analysis of the prospects for the formaion of a neo-industrial economy on the example of Ukraine - Pidlisna, Olena (Technology audit and production reserves, 2020)
The object of research is industry as a type of economic activity and features of its transformation towards neo-industrialization. The paper presents the results of a study of the dynamics of changes in the results of economic activity on the example of the Ukrainian industry as a separate sector of the national economy. In the course of the study, methods of analysis, comparison and generalization were applied. The content of the concept "structural and logical chains of industrial enterprises" in the formation of added value is revealed. It shows how a change in the view of production chains can contribute to the formation of a growth economy. The market economy presupposes the proactive determination by the owner of the enterprise of promising areas of development. But in the conditions of the loss by the state of the strategic vector of its development in the economy, there is an imbalance and intersectoral conflicts. The author investigated the dynamics of the development of certain areas of industry in Ukraine, an attempt was made to form structural and logical chains of mutual support and mutual stimulation of industrial enterprises of individual sections and sections of types of economic activity. It is shown how the principles of the "push-pull" approach function when determining the directions of the state's industrial policy. It is noted that the formation of structural and logical chains of industrial enterprises can be used as the basis for investment and innovation roadmaps of the state. The scientific novelty of the work lies in the determination of approaches to the formation of a strategy of state industrial policy using a retrospective analysis of the dynamics of changes by type of economic activity. An enlarged analysis of statistical dynamics is proposed, which makes it possible to move from operational and tactical planning of economic policy to strategic one. The practical value of the work lies in an attempt to show the structural and logical relationships between certain types of economic activity, which determine the prospects for the formation of investment and innovative roadmaps for the development of Ukrainian industry. Taking into account the tendencies and prospects of the neo-industrialization of the world economy, the directions are shown in which the Ukrainian industry can keep the national economy, form regional positions and take a worthy place in the world economic system.